A new partially hydrolyzed whey-based follow-on formula with age-adapted protein content supports healthy growth during the first year of life - Billeaud, Claude; Adamon, Latif; Piloquet, Hugues; Hays, Nicholas P.; Dupuis, Lénaïck; Metreau, Isabelle; Léké, André (Frontiers in Pediatrics, 2022)
Background: Standard infant formulas often have higher protein content than breastmilk in order to compensate for potentially lower digestibility; excess protein intake may promote adverse effects later in life. A new partially hydrolyzed whey-based (pHF-W) follow-on formula (FoF) with age-adapted protein content was evaluated for growth and gastrointestinal (GI) tolerance in healthy infants. Methods: Formula-fed (FF) infants (n=108) received standard pHF-W formula (1.9g protein/100 kcal) from enrollment (age ≤30 days[d]) until age 120d followed by new pHF-W FoF (1.6g protein/100 kcal) until 360d. Weight gain velocity (WGV) (mean daily WG from enrollment to age 180d) was compared to WHO growth standards and a breastfed (BF) reference group (n=86) (non-inferiority margin –3g/d). GI tolerance was assessed using a validated questionnaire (scale range 13-65). Results: WGV in FF infants (mean±SD 24.0±4.4 g/d) was non-inferior to BF (23.7±3.9 g/d) and WHO standards (all p≤0.013). Weight-for-age, length-for-age, weight-for-length, and head circumference-for-age z-scores of FF infants were not significantly different from BF at any timepoint. Symptoms of GI intolerance were low (≤23) at all timepoints and similar between groups. Conclusions: A new pHF-W FoF with age-adapted protein content fed sequentially after standard pHF-W infant formula is safe, well-tolerated, and promotes a healthy growth pattern consistent with BF infants and WHO standards during the first year of life. This trial was registered on clinicaltrials.gov as NCT03276663.